Conteúdo adulto e masculinidades em rede: um estudo sobre os perfis +18 do Twitter - Costa, David Nogueira da (2022)
This research has as objective to investigate the Twitter “+18 profiles” phenomenon, accounts created by users with the intention to use the platform to establish sexual-affective interactions and display their sexual experiences through pictures, texts and videos. The research focus is on men who make this use to publicize their work as professionals of the gay sexual market. The research wants to comprehend how this online interactions change and authorize certain social markers, such as body, sexuality and gender performances on the web and outside of it too. Beyond that, seeks to understand how the operations of this profiles group are influenced by capitalist dynamics and it’s effects and how the productions of bodies and performances looking for visibility and engagement happens. The research is made through online observations, with a specific account created for this purpose. The reflections are written in a field journal, accompanied by prints with critic analyses of the content published on the platform. Conceptually, the research is sustained by the sexual scripts by John Gagnon and William Simon (1986; 2006), the gender advertisements by Erving Goffman (1987), the pharmacopornographic regime and gender technologies by Paul Preciado (2018; 2020) and Teresa de Lauretis (1994) and the transparency society by Byung-Chul Han (2015; 2017) tu understand how the contemporary economic order produces material and symbolic capital through bodies excited and incited to make pleasure, enjoyment and high performances. Furthermore, I’m also supported by Nick Srnicek (2017), Thomas Poell, David Nieborg and José Van Djick (2020), Peter Golding and Graham Murdock (2002) to grasp the inner workings of a digital platforms market that produces capital through data of our most intimate life. Moreover, studies by Richard Miskolci (2009; 2013; 2014), Larissa Pelúcio (2017) and Carolina Parreiras (2007; 2008) serve as references and guides of how to conduct an online ethnography, taking in account the ethic, methodologic and theoric questions that appear in researches of this nature.